PSEUDOSINHALITE: DISCOVERY OF THE HYDROUS MGAL-BORATE AS A NEW MINERAL IN THE TAYOZHNOYE, SIBERIA, SKARN DEPOSIT - Schreyer W.; Medenbach O.; Burchard M.; Dettmar D.; Pertsev N.N. (My University, 1998)
After its initial synthesis as the new compound Mg2Al3B2O9(OH) (Daniels et al. 1997) pseudosinhalite has now been discovered as a new mineral. It occurs, together with hydrotalcite, as a replacement product of sinhalite, MgAlBO4, in an impure marble of the contact metasomatic iron boron deposit of Tayozhnoye in the Aldan Shield of Siberia. Its chemical composition determined by electron microprobe is (wt%): Al2O3 46.88; MgO 25.12; FeO 1.99; B2O3 (calculated) 21.75; H2O (calculated) 2.81 giving a total of 98.55 and leading to the empirical formula (Mg2.00 Fe2+ 0.09)Σ=2.09 Al2.94 B2O9(OH). The small deviation from the ideal stoichiometry with (Mg + Fe2+):Al ≠ 2:3 may be caused by either solid solution towards, or submicroscopic interlayering with lamellae of, the structurally similar mineral sinhalite. The underlying substitution involving also B and H would be (Mg + Fe)+ B=Al+2H. Pseudosinhalite is monoclinic, space group P21/c, with a=7.49(1), b=4.33(1), c=9.85(2) ; β=110.7(1); V = 299(1) 3; Z = 2. Calculated density is 3.508 g/cm3. Pseudosinhalite is colourless with white streak and has a vitreous lustre. It is transparent; no fluorescence was detected. There is no cleavage and parting; fractures are concoidal. Optical constants could not be measured properly due to polysynthetic microtwinning, but αV=80. The temperature of pseudosinhalite formation was below about 400 C at low pressures and with a hydrous, CO2-bearing fluid participating in the reaction.